Heavy Metal Immobilization by Phosphate-Solubilizing Fungus and Phosphogypsum Under the Co-Existence of Pb(II) and Cd(II) - Xu Li; Zhenyu Chao; Haoxuan Li; Jiakai Ji; Xin Sun; Yingxi Chen; Zhengda Li; Zhen Li; Chuanhao Li; Jun Yao; Lan Xiang (Agronomy, 2025)
Globally, phosphogypsum (PG) is the primary by-product of the phosphorus industry. Aspergillus niger (A. niger), one of the most powerful types of phosphate-solubilizing fungi (PSF), can secrete organic acids to dissolve the phosphates in PG. This study investigated heavy metal (HM) remediation by PG and A. niger under the co-existence of Pb and Cd. It demonstrated that 1 mmol/L Pb2+ stimulated the bioactivity of A. niger during incubation, based on the CO2 emission rate. PG successfully functioned as P source for the fungus, and promoted the growth of the fungal cells. Meanwhile, it also provided sulfates to immobilize Pb in the solution. The subsequently generated anglesite was confirmed using SEM imaging. The immobilization rate of Pb reached over 95%. Under co-existence, Pb2+ and 0.01 mmol/L Cd2+ maximized the stimulating effect of A. niger. However, the biotoxicity of Pb2+ and elevated Cd2+ (0.1 mmol/L) counterbalanced the stimulating effect. Finally, 1 mmol/L Cd2+ dramatically reduced the fungal activity. In addition, organic matters from the debris of A. niger could still bind Pb2+ and Cd2+ according to the significantly lowered water-soluble Pb and Cd concentrations. In all treatments with the addition of Cd2+, the relatively high biotoxicity of Cd2+ induced A. niger to absorb more Pb2+ to minimize the sorption of Cd2+ based on the XRD results. The functional group analysis of ATR-IR also confirmed the phenomenon. This pathway maintained the stability of Pb2+ immobilization using the fungus and PG. This study, hence, shed light on the application of A. niger and solid waste PG to remediate the pollution of Pb and Cd.